Reconstructing Indonesia’s Electoral System from the Perspective of Maqasid al-Shari’ah: A Critical Evaluation of Proportional Representation Models - Ahmad Senang; Muhammad Ramadhan; Arifuddin Muda Harahap (Program Pascasarjana IAIN Langsa, 2026)
Indonesia's electoral system remains a subject of academic and political debate, particularly regarding the effectiveness of open-list and closed-list proportional representation systems in establishing a representative, accountable, and public-oriented democracy. Previous studies have predominantly examined these electoral models from the perspectives of constitutional law, political participation, and democratic institutionalization. However, limited attention has been given to evaluating electoral systems from a substantive perspective concerning the achievement of public welfare and the prevention of political harms. Therefore, this study employs maqāṣid al-sharīʿah as an evaluative framework to assess the quality and consequences of electoral systems. This study aims to analyze the strengths and weaknesses of open-list and closed-list proportional representation systems and to formulate a reconstruction model of Indonesia's electoral system oriented toward public welfare. This research applies a normative legal method using statutory, conceptual, and comparative approaches. Data were collected through library research and analyzed qualitatively using a descriptive-analytical method. The findings indicate that while the open-list proportional system strengthens voter sovereignty, it also creates challenges, including vote-buying, high political costs, economic-political oligarchy, and electoral corruption. Meanwhile, the closed-list proportional system provides stronger party institutionalization but requires transparency and internal party democratization. This study contributes to developing maqāṣid al-sharīʿah as an evaluative framework for reconstructing modern electoral systems based on justice, accountability, and public welfare.